PENGARUH MODEL PEMBELAJARAN VALEU CLARIFICATION TECHNIQUE (VCT) TERHADAP SIKAP SOSIAL PESERTA DIDIK - Roy Kembar Habibi; Tegar Pambudi; Ulfa Nurfitria Ardila; Maya Adina (STKIP Subang, 2026)
Social attitude is an internal tendency that directs how a person evaluates, feels, and behaves in relation to others and society. The problem in this study is the low level of social attitudes among fifth-grade students at State Elementary School 5 Kemiling Permai. This study aims to: (1) determine the effect of the Value Clarification Technique (VCT) learning model on students' social attitudes; (2) determine the difference in students' social attitudes between the experimental class using the Value Clarification Technique (VCT) learning model and the control class using the problem-based learning model. This research uses a quantitative approach with a quasi-experimental research type and a non-equivalent control group research design. The study population is the fifth-grade students of State Elementary School 5 Kemiling Permai. The sampling technique used purposive sampling with a sample of 43 students in class VB as the experimental group and VA as the control group. The data analysis results show: (1) there is a significant influence of the Value Clarification Technique (VCT) learning model on students' social attitudes, with the help of SPSS 25, the significance value obtained is less than 0.05 (0.000 < 0.05), so Ha is accepted, (2) there is a significant difference in learning using the Value Clarification Technique (VCT) model compared to learning with the problem-based learning model.